Nano-structural analysis of fish collagen extracts for new process development - Jaswir, Irwandi; Monsur, Hammed Ademola; Mohd. Salleh, Hamzah (Academic Journals, 2011)
Nano and micro imaging were used to evaluate effects of pretreatment solution on gelatin. Four types of pretreatment solution were used during fish gelatin extraction in this study. They are acetic acid (A), acetic acid-NaCl (SA), acetic acid-NaOH (BA) and acetic acid-NaOH-NaCl (SBA). Different patterns were observed for different gelatins pretreated. Results show that each pretreatment gave different nano imaging patterns: A (fibril), SA (zig-zag cracks), BA (straight rods) and SBA (cross-linked rods). Crosslinked rods observed in SBA denote adequate removal of non-collagen content of the fish skin and increased its surface area. SBA is suggested as the best pretreatment for perch fish gelatin. The result of viscosity was also highest for sample SBA (0.0245 ± 0.0001 pas), while viscosity for others are 0.0155 ± 0.0002, 0.0123 ± 0.0001 and 0.0025 ± 0.0001 pas for samples BA, SA and A, respectively. SDS-PAGE analysis showed the presence of and in samples SBA and BA.